Peningkatan Hasil Belajar Ekonomi melalui Pembelajaran Group Investigation Kelas XI IPS 1 SMA Negeri 13 Pekanbaru - Neneng Yuyu Rohana (Journal on Education, 2022)
This research was compiled with the aim of knowing the increase in economic learning activities for Class XI IPS1, through Group Investigation learning. This research was conducted from July to September 2017. The research subjects were 30 students of class XI IPS1 at SMA Negeri 13 Pekanbaru, consisting of 15 boys and 15 girls. The type of research used is classroom action research. This research was conducted in two cycles for six meetings and two meetings for learning achievement tests. At each meeting, learning was carried out using the group investigation method with six stages, namely identifying topics and organizing students into groups, planning tasks to be studied, carrying out investigations. Prepare final reports, present final reports, draw conclusions and evaluate stages. The research findings show that the use of the Group Investigation method can improve the results of studying economics in class XI IPS2 SMA Negeri 13 Pekanbaru. This increase can be seen in the results of the first cycle with an average value of 77.50% to 86.67% in the second cycle. The percentage of students who passed with grades increased from 63.33% to 86.67%. In general, the learning process in action research that has been carried out to improve learning outcomes is optimal.